Old age representations in Constanze Dennig’s dystopia “Exstasy Rave” - Gaidash, Anna; Kadubovska, Svitlana (Studia Philologica, 2021)
The paper tackles the representations of old age in Constanze Dennig's dystopia "Exstasy Rave". Modern theatrical tendencies and the role of drama as a mouthpiece of social ideas, in particular in matters of aging and old age, are related; ageist stereotypes in the text of Constanze Dennig are analyzed; problem-semantic aspects of corporeality are studied; the possibilities of author's remodeling of discriminatory stereotypes of old age are inferred. The challenges presented by the Austrian woman playwright in her drama allow us to attribute her work to the post-dramatic theater, which in Lehmann's sense is able to help restore the social continuum and support society's internal unity. Through the mouths of the protagonists and the nonverbal plane, Dennig's drama becomes a means of communication in society. The analyzed age stereotypes of the play reveal the author's reflection on the social challenges of modern Western society, including the attitude to the third age and the aging process. In the dystopia, old age is perceived as a physical and moral decline and a burden on society. In the future, discriminatory practices against the older generation are not only verbal, but also physical (forced euthanasia). There are manifestations of self-stereotyping by the aged dramatis personae themselves. Carefully read problem-semantic aspects of corporeality in a dramatic text are a segment of ageist discourse, sometimes with a political color. Yet, the woman playwright offers mechanisms for remodeling the ageist consciousness by means of the female characters (Eva, Michaela). Dennig constructs a sharply negative vision of the potential consequences of the ageist attitude towards the elderly because she observes their roots in the socio-economic and moral-ethical issues of today. Thus, old age is a litmus test for the social morality of Europeans, who set an example to the younger generation with their attitude to old age. Key words: aging, elderly characters, ageism, dystopia, Constanze Dennig, “Exstasy Rave”, corporeality.